Assessing the use of Polyethylene Terephthalate fibre in reinforcement of lime-stabilised expansive soils - Mark Manana (Uganda Christian University, 2024)
Expansive soils are soils associated with constant volumetric change due to alternations in the moisture present in such soils, and such volume variations can lead to the expansive soils being unsuitable for use as subgrade material. The research was focused on the use of Polyethylene Terephthalate fibre in the reinforcement of hydrated limestabilised expansive soils to improve the properties of these soils. The research had specific objectives which were achieved by following a methodology that had implemented laboratory tests such as Sieve analysis, Atterberg Limits, California Bearing Ratio, Unconfined Compressive Strength, Free Swell Index, and Proctor Compaction on the neat soil along with other samples with a constant 6% content of Lime and varying percentages of fibre from 0 % to 2 %. There was a Tensile strength test done on the fibre. The tests were done following a given set of standards, after which the results on the neat sample found the soil to be expansive clayey soils and the fibrereinforced soil that was lime stabilised had the optimum mix ratio of 6% lime and 1.5 % fibre. The optimum mix ratio had a California Bearing Ratio of 54 % and an Unconfined Compressive Strength of 0.59 MPa. The results of the soil mixed with 1.5 % fibre and 6 % lime all matched the standards of subgrade material according to the Ministry of Works and Transport, General Specifications for Road and Bridge Works, 2005 manual. This implied that hydrated lime and Polyethylene Terephthalate fibre can be implemented in the improvement of properties of expansive soils to acceptable standards for subgrade material. There is a need for more research into the use of other fibres in the reinforcement of lime-stabilised soils.